Diversity of Canna on Enggano Island, Bengkulu Province - Evelyne Riandini; Eki Susanto; Nur Fitria Febrianti (Jurnal Biologi Tropis, 2023)
Cannaceae is only genus Canna. The origin of Canna was South America, it dispersed and cultivated in tropical areas of the world. The diversity of Canna particularly in Enggano Island is not known well. This research was to provide the update information of Canna in Enggano Island. The study used exploration method. The result of research was found 1 species of Canna indica L. and 3 variation cultivar Canna hybrida (‘Yellow King Humbert’, ‘Fire Red’, and ‘Ra’). C. indica L. and C. hybrida have differences in terms of utilization. C. indica L. was utilized as food plant. Peoples utilized rhizome of C. indica L. as food alternative. C. hybrida was utilized as ornamental plant. C. hybrida known as ornamental plant due to their flower colors.